Diazananographene with Quadruple [5]Helicene Units: Synthesis, Optical Properties, and Supramolecular Assembly - Ma, Xiao-Hui; Xing, Jiang-Feng; Chai, Ling; Deng, Qing-Song; Chen, Xuan-Wen; Su, Hai-Feng; Li, Chao; Tan, Yuan-Zhi (Organic Materials, 2024)
A helical diazananographene (1) was successfully synthesized by employing sterically hindered t-butyl groups to inhibit further dehydrocyclization of [5]helicene units. These t-butyl groups stabilized the conformation of [5]helicene units, thus resulting in three stable conformers of 1, comprising a pair of enantiomers (1-(P, P, P, P) and 1-(M, M, M, M)) and a mesomer (1-(P, P, M, M)). In comparison to its planar analogs, helical 1 exhibited broadened peaks in both its absorption and emission spectra, leading to an increase in the emission quantum yield from 0.3 to 0.6. The significantly enhanced radiative decay rate (kr) accounted for the increase in the quantum yield of 1. Additionally, it was observed that the compound could be fully protonated upon the addition of an equivalent acid. Furthermore, 1 assembled into a chiral trimeric metallosupramolecular complex upon coordination with the PdII units. Both protonated 1 and the metallosupramolecular complex exhibited an enhanced circular dichroic response. These findings revealed that the incorporation of a helical structure and pyridinic nitrogen-doping into the nanographene can allow the synthesis of responsive chiroptical graphenic materials, which could serve as fundamental components for constructing chiral hierarchical metallosupramolecular structures.
Keywords: diazananographene; [5]helicene; optical properties; supramolecular assembly